Age-Dependent Changes on Reproductive Potency of Female Rainbow Trout (Oncorhynchus mykiss, Walbaum1792) in Kashmir - Latief, Tamana; Bhat, Farooz Ahmad; Shah, Tasaduq Hussain; Abubakr, Adnan; Bhat, Bilal Ahmad; Chesti, Anayitullah (Fishery Technology, 2026)
Rainbow trout, Oncorhynchus mykiss is extensively cultured in the Himalayas owing to its hardy nature, suitability for sport fishing, high meat quality and ease of breeding. In this study, the age-dependent reproductive performance of female rainbow trout specimens collected from Trout fish farms of Kashmir, were studied with the aim to gain insights into its breeding characteristics and to inform thedevelopment of an optimal brood-stock managementplan. The age of the specimens ranged from 0+ to 3+ years. Fish age showed a significant correlation with total length, total weight, ovary length, ovary weight and GSI. Fecundity was only observed in age 3+. The absolute fecundity of the fish in age 3+ ranged from 320 to 585 eggs, while relative fecundity ranged from 0.873 to 1.703 eggs/g body weight and the ova diameter recorded ranged from 3.11 to 4.68 mm. Histological examination showed that ovaries were in the early stage of development in age 0+; contained young oocytes in age 1+; exhibited oocytes at different developmental stages in age 2+; and were fully mature with oocytes at the yolk deposition stage in age 3+. Based on GSI values, ova-diameter and histological examinations, age 3+ was identified as the spawning age group.